2005
DOI: 10.1016/j.hepres.2005.08.005
|View full text |Cite
|
Sign up to set email alerts
|

Upregulation of hepcidin by interleukin-1β in human hepatoma cell lines

Abstract: Anemia of chronic disease (ACD) is commonly observed in chronic inflammation, although its pathogenesis is poorly understood. Hepcidin is thought to be a key regulator in iron metabolism and has been implicated in ACD. Although the induction of hepcidin by an inflammatory cytokine interleukin-6 (IL-6) seems to have been confirmed, it is still controversial whether interleukin-1beta (IL-1beta), also known as an inflammatory cytokine, regulates hepcidin expression. We demonstrated that hepcidin mRNA was upregula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
21
1

Year Published

2007
2007
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(23 citation statements)
references
References 45 publications
(61 reference statements)
1
21
1
Order By: Relevance
“…TNF-a and IL-1h levels may be also elevated in myeloma (17 -19) and both have been implicated in regulating hepcidin expression (11,20,21). Thus, we also measured these cytokines in the sera of our patients.…”
Section: Resultsmentioning
confidence: 99%
“…TNF-a and IL-1h levels may be also elevated in myeloma (17 -19) and both have been implicated in regulating hepcidin expression (11,20,21). Thus, we also measured these cytokines in the sera of our patients.…”
Section: Resultsmentioning
confidence: 99%
“…However, the hepcidin responsiveness to LPSs was maintained to some extent in IL-6-knockout mice [33], indicating that the LPS-induced expression of other inflammatory cytokines is responsible for the upregulation of hepcidin expression. Although IL-1 has been shown to play a role in the upregulation of hepcidin expression [12,13], other inflammatory cytokines might be involved in hepcidin synthesis. Suda et al [23] demonstrated that the stimulation of human monocytes and dendritic cells with LPS or fixed Staphylococcus aureus increased the production of OSM, suggesting that OSM could be upregulated in inflammatory conditions.…”
Section: Discussionmentioning
confidence: 99%
“…In response to iron loading, hepatocytes produce hepcidin to maintain iron homeostasis [8,9]; lack of hepcidin leads to the development of hereditary hemochromatosis that is characterized by excessive absorption of dietary iron and pathological increase in body iron stores [10,11]. Hepatic expression of hepcidin is also upregulated by inflammatory cytokines, including interleukin-6 (IL-6) [9,12] and IL-1 [12,13]. In vitro studies have demonstrated that hepcidin exerts antimicrobial effects on various bacteria [1,2].…”
Section: Introductionmentioning
confidence: 99%
“…Stimuli such as hypoxia, erythropoiesis, iron levels, and inflammation control the expression of this gene. During anaemia related to chronic disease, gene expression is increased [11]. Several studies have demonstrated the influence of the serum hepcidin concentration on the pathogenesis of diseases such as juvenile hereditary haemochromatosis, in which a polymorphism present in the HAMP gene promotes hepcidin synthesis deficiency with iron accumulation in the tissues [12,13,14].…”
Section: Introductionmentioning
confidence: 99%